"Our ladies" versus "our dominators": Gender differences and nationalist discourse in the Polish Olympic coverage - Organista Natalia; Mazur Zuzanna; Dóczi Tamás (Sciendo, 2020)
The article presents differences in describing sportspeople during the last four Olympic Games in terms of gender and nationality in Polish newspapers. The fundamental goal of the research was to perform the quantitative and qualitative comparison of press materials from four Olympics (Vancouver 2010, London 2012, Sochi 2014, Rio de Janeiro 2016). The content analysis was used for the quantitative part of the study and critical discourse analysis of two newspapers (the broadsheet and tabloid) in Poland for qualitative part. 712 media articles were analyzed. Our analysis has revealed significant underrepresentation of women and also differences in the description of rival competitors as well as overrepresentation of articles about Polish representatives during the Olympics. Those articles dwelt on the issue of nationality much more often and were more emotionally charged. Also, to a great extent, the performance of non-Polish women athletes was left unconsidered. The authors therefore indicate the validity of combining gender analysis and nationality in the context of the Olympic Games.